Sliding-Mode Observer for Speed and Position Sensorless Control of Linear-PMSM - Kazraji Saeed Masoumi; Soflayi Ramin Bavili; Sharifian Mohammad Bagher Bannae (Electrical, Control and Communication Engineering, 2014)
The paper presents a sliding-mode observer that utilizes sigmoid function for speed and position sensorless control of permanent-magnet linear synchronous motor (PMLSM). In conventional sliding mode observer method there are the chattering phenomenon and the phase lag. Thus, in order to avoid the usage of the low pass filter and the phase compensator based on back EMF, in this paper a sliding mode observer with sigmoid function for detecting the back EMF in a PMLSM is designed to estimate the speed and the position of the rotor. Most of conventional sliding mode observers use sign or saturation functions which need low pass filter in order to detect back electromotive force (back EMF). In this paper a sigmoid function is used instead of discontinuous sign function to decrease undesirable chattering phenomenon. By reducing the chattering, detecting of the back EMF can be made directly from switching signal without any low pass filter. Thus the delay time in the proposed observer is eliminated because of the low pass filter. Furthermore, there is no need to compensate phase fault in position and speed estimating of linear-PMSM. Advantages of the proposed observer have been shown by simulation with MATLAB software.